Multiplicador local do emprego: Mesorregi\~oes Brasileiras (2000-2010) - Guilherme Matoso Macedo; Leonardo Monasterio (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This paper estimates the local employment multiplier for Brazil (2000-2010). The methodology is based on Moretti (2010) and Moretti and Thulin (2012) who estimated these multipliers for the U.S. and Sweden. We have estimated the impacts of changes in employment in the tradables sectors on the employment of the non-tradables sectors, as well as the impact of changes in employment in high-tech and low-tech tradable sectors on the employment of the non-tradable sectors. We created Instrumental variables based on shift-share methodology. The employment data covers 21 economic subsectors and 123 regions in 2000, 2005 and 2010. In the baseline model, for each new job in the tradable sectors, 4.0 jobs were created locally in the non-tradable sectors. Also, it was estimated that each job in the high-tech tradable sectors creates 6.9 jobs in the non-tradable sectors in the long term.
Keywords: J21; J88; R12; R23; 330; regional economics; labor market; local multipliers; shift-share